RISK MANAGEMENT, AUDIT AND INTERNAL CONTROL - L. B. Alikulova,; N. N. Nurmukhametov,; L. M. Sembiyeva,; D. A. Pankov, (Scientific Journal of Pedagogy and Economics, 2019)
Micro and micro risk management has become more relevant in recentyears due to increased turbulence in the markets and global financial instability. Acceleration of technology-related innovation processes also makes a definite contribution to increasing relevance of the topic. The pace of production processes and the speed of management decision-making are increasing. Company risk management can be vividlycompared to a brake gear of racecar. The task of effective risk management system is not about slowing down the pace, but rather ensuring safety in tight bends.